Hubungan Manusia dan Tuhan Dalam Puisi Klasik Religi Karya Taufiq Ismail, Amir Hamzah, dan Emha Ainun Najib - Azzahra, Safira; Haryanti, Novi Diah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study is to find out and to make an analogy of the poet's visualization of three different poems with religious genres. The themes raised in the poetry are also different, there are also poems with the theme of people's struggle, the theme of human greed for nature, as well as religious themes whose meaning is often revealed implicitly in poetry. This study uses qualitative research using a comparative literature approach. The data taken in this study are the text of the poem